DETERMINAN KREDIT BERMASALAH PADA BANK DEVISA DI INDONESIA - Evi Sistiyarini; Ririn Poerwanti (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2021)
This study aims to examine and analyze the factors which effect problem credit in Indonesia foreign exchange banks. The dependent variable is NPL. The independent variables consist of CAR, LDR, NIM, BOPO, interest rate and inflation. The data uses a secondary data with the documentation method. The populations of this study are all of the foreign exchange banks. There are 33 bank sample in this study. This research used panel data regression. The results showed that CAR, LDR, NIM, BOPO, interest and inflation simultanously have a significant effect on NPL. CAR, LDR, and BOPO variables partially have a negative effect but not significantly on NPL. NIM partially has a positive effect and not significant on the NPL. Interest rate partially has a significant positive effect on the NPL. The inflation variable partially has a significant negative effect on the NPL.